Performance of different techniques of generation and absorption of free-surface waves in Computational Fluid Dynamics. (15th October 2020) - Choi, Young-Myung; Kim, Young Jun; Bouscasse, Benjamin; Seng, Sopheak; Gentaz, Lionel; Ferrant, Pierre
Abstract: In wave-structure interaction problems, the minimization of wave reflection at boundaries is important for achieving accurate results and limiting the disturbances on the air/water interface. The present study compares a set of existing wave outlet techniques which are commonly applied in free surface simulations using a viscous flow solver. These techniques are stretched mesh, linear damping source, increased viscosity, and relaxation schemes. The comparisons are performed for test conditions which include propagation of regular incident waves and damping of radiation waves. Highlights: The wave generation/absorption techniques for marine application commonly used in CFD are reviewed and tested with benchmark test cases. The CFD solver based on the finite volume method (FVM) with a volume of fluid (VOF) is studied. A convergence study performed to assess the quality of simulation is presented. Parametric studies on the different wave absorption techniques are conducted for the wave propagation in the numerical wave tank. The wave reflection coefficients for different techniques are compared and the results are discussed. A swaying 2D Lewis form is considered with different size of computational domain and outlets. The influence of the outlet setting in the computed radiation forces is discussed.